Certification and potential future use of the reference standard designed for the test system for determination of the fractional (antigenic) composition of human serum products by immunoelectrophoresis - O. G. Kornilova; I. L. Arefyeva; E. S. Konovalova; R. A. Volkova; O. V. Fadeykina; E. Yu. Kudasheva; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article gives an account of certification performed for a new batch of a Reference standard to be used with the test system for determination of the fractional (antigenic) composition of human serum products by immunoelectrophoresis -industry reference standard (IRS) 42-28-77 - in accordance with existing requirements. A candidate reference standard was represented by a batch of normal human serum intended for diagnostic purposes (more than 500 donors) and a batch of immunoelectrophoresis serum against human serum proteins (antiserum against human serum proteins). In accordance with the certification programme, the fractional (antigenic) composition of the reference standard was determined by immunoelectrophoresis using «KliniTest-EF» buffer and 0.05 M borate buffer solution and the modes stipulated in the general monograph 1.8.2.0002.15 Agar gel immunoelectrophoresis. The reaction between the antiserum against human serum proteins and the normal human serum components of the reference standard produced at least 15 precipitation lines. The study demonstrated that the bromphenol blue dye could be used together with «KliniTest-EF» buffer to assess albumin migration, and the pyronin B dye could be used together with «KliniTest-EF» buffer and 0.05 M borate buffer solution to assess immunoglobulin migration. The study confirmed the applicability of the certified reference standard designed for the test system for determination of the fractional (antigenic) composition of human serum products by immunoelectrophoresis, and set the criteria for its use in the context of human serum products identification (species specificity) testing not only by immunoelectrophoresis, but also by agar-gel immunodiffusion.